Ответ:
Объяснение:
a^{-9}/a^{-7}=a^{-9-(-7)}=a^{-9+7)}=a^{-2}=1/a^2
[
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
a^{-9}/a^{-7}=a^{-9-(-7)}=a^{-9+7)}=a^{-2}=1/a^2
[![\frac{a^{-9}}{a^{-7}}=a^{(-9-(-7)}=a^{(-9+7)}=a^{-2}=\frac{1}{a^{2}} \frac{a^{-9}}{a^{-7}}=a^{(-9-(-7)}=a^{(-9+7)}=a^{-2}=\frac{1}{a^{2}}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%5E%7B-9%7D%7D%7Ba%5E%7B-7%7D%7D%3Da%5E%7B%28-9-%28-7%29%7D%3Da%5E%7B%28-9%2B7%29%7D%3Da%5E%7B-2%7D%3D%5Cfrac%7B1%7D%7Ba%5E%7B2%7D%7D)